Imitation Learning dalam Seting Bimbingan Kelompok untuk Mereduksi Perilaku Agresif Anak - Hananda Fitra Pranatha; Adif Jawadi Saputra; Muhammad Ubaidillah (UIN Siber Syekh Nurjati Cirebon, 2024)
This research addresses the growing concern of aggressive behavior in children, recognizing it as a pressing issue that needs attention. Our focus is on exploring effective methods to mitigate this behavior through group guidance services that incorporate imitation learning techniques. This study aims to provide empirical evidence on the effectiveness of these techniques in reducing aggression within a group context. Following the implementation of our services for the experimental group, we conducted thorough statistical analyses using the Mann-Whitney test. The outcome presented an Asymptotic Significance value (2-tailed) of 0.501, indicating that there was no statistically significant change in behavior following the intervention. Nevertheless, when we analyze the observations and the individual post-test scores of each participant in the experimental group, it becomes evident that imitation learning techniques hold promise in decreasing aggressive behavior among children. With further refinement and application, this approach could serve as a valuable tool in fostering a more positive behavioral trajectory for children facing these challenges.